Effect of using Different Remineralizing Agents on Micro-shear Bond Strength of Nanohybrid Composite Resin - Alagha, Ebaa I. (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: This study was conducted to evaluate the effect of different remineralizing agents on micro-shear bond strength (SBS) of nanohybrid composite resin to dentin. METHODS: Thirty-six human molars were divided into four main equal groups (nine teeth each) according to the type of remineralizing agent used; nanohydroxyapatite, sodium fluoride, fluorohydroxyapatite, and control without remineralizing agent. Each group was divided into three equal subgroups (three teeth each) according to the storage time; 1 day, 1 month, and 3 months. Specially fabricated cylindrical plastic mold was made, and teeth were embedded vertically in the mold to the level of cementoenamel junction of the tooth leaving the occlusal surface projecting above the surface of the mold. Cylindrical fissure carbide bur was used in teeth preparation. Teeth were trimmed perpendicular to the long axes of them. Demineralizing agents (Nano hydroxyapatite, sodium fluoride, and fluorohydroxyapatite) were applied then adhesive system applied then composite resin was applied using five sections of a pediatric intravenous tube to act as molds for composite specimen then the specimens stored in artificial saliva at 37°C for different storage times in an incubator. The micro-SBS was assessed using universal testing machine. Then, the mode of failure for each group was determined using stereomicroscope device. Then, the obtained data were tabulated and statistically analyzed. One-way ANOVA was used to compare between more than two non-related samples. The significance level was set at p ≤ 0.05. Statistical analysis was performed with IBM SPSS Statistics. RESULTS: There was statistically significant difference between the four studied groups regarding bond strength at different storage times. Fluorohydroxyapatite had the highest bond strength mean values followed by nanohydroxyapatite, while the lowest value was the sodium fluoride group. CONCLUSION: Fluorohydroxyapatite and nanohydroxyapatite had a positive effect on micro-SBS to dentin, but sodium fluoride had a negative effect. The storage time increase had a positive effect on the micro-SBS of dentin with fluorohydroxyapatite and nanohydroxyapatite, also it had adverse effect on the dentin bond strength with sodium fluoride and control groups.